Protein Extraction from Arthrospira platensis for Use in Food Processing - Elisa Costa; Miguel Ribeiro; Luís Filipe-Ribeiro; Fernanda Cosme; Fernando M. Nunes (Medical Sciences Forum)
Algae protein has emerged as a sustainable and non-allergenic alternative to animal protein as the market seeks to reduce reliance on traditional animal protein sources. To effectively utilize algae protein isolates, particularly from Arthrospira platensis, it is essential to develop an efficient method for protein extraction and isolation that can be scaled up. This work aims to optimize the extraction conditions to obtain high-purity protein extracts. HPLC-DAD was used to determine the total and free amino acid profiles, while SDS-PAGE and HPLC-MS/MS were used for the protein characterization. An optimized extraction method was selected based on achieving the highest protein content and purity.